The everlasting crisis: Representing the contemporary Athenian cityscape. Issue 2 (1st October 2019) - Petsini, Penelope
Crisis recontextualized numerous visual projects, regardless of their authors' intentions or their initial context of production. Eventually framing our perception of visual production, including the photographic, crisis can now be detected even within pictures and visual narratives which diligently avoid depicting it, or reflect it at a tangent. Expanding on this perception, in this visual essay I will discuss a mode of photographic documentation and interpretation of the Greek crisis in which urban space engages with the recent sociopolitical situation, albeit not always in a straightforward manner. In the first part, I briefly discuss the current context of photography output in Greece, focusing on photographers who made urban space central to their exploration of recent conditions. What many of them share, I argue, is an interest in the commonplace, an aspect of urban landscape which used to be dismissed as insignificant and without interest. I then focus on Nikos Panayotopoulos's research project Terra Cognita, which I examine as a trailblazing example of this trend. Thoroughly documenting Athens from early 2000 until the end of 2008, namely the period before, during and after the so-called 'glory days' of the 2004 Olympics, and portraying a landscape already in decline, this project came to suggest that crisis was here long before we recognized it as such.